Analisis Kesesuaian Dan Daya Dukung Wisata Pantai Binasi Kecamatan Sorkam Barat Kabupaten Tapanuli Tengah - Hasnina Malasari Pasaribu; Pindi Patana; Syammaun Usman (AQUACOASTMARINE, 2017)
Binasi Beach is located in Tapanuli Tengah district and has potentially to be developed as a tourism object. This research aimed to analyze the suitability level of coastal tourism which is reviewed based on the carrying capacity of Binasi Pantai area and to know perception tourists. It was conducted on February - March 2017. The data collection technique used is purposive sampling, divided into three stations. Analysis of data used analysis of the suitability of tourism, assessment of the suitability of tourism activities, the carrying capacity of the area, and the perception of tourists. Results of swimming suitability analysis on the three stations have the same category as very suitable (S1). Conformity Index value for recreational tourism on the three stations has the same category as very suitable (S1). Different value of Boating station resulted category 1 as appropriated category (S2) while, station 2 has very suitable category (S1), station 3 has inappropriated category (S3). Carrying capacity of the Binasi Beach can accomodate 1.548 tourists every day. The tourist marked the Binasi Beach area with beautiful natural scenerly (79%) and comfortable (68%).Keywords: Analysis of the carrying capacity region, Binasi beaches, Land suitability assessment, Suitability analysis, The perception of tourists.